The Practice of Home-based Direct Observer Treatment of Patients with Positive Pulmonary Tuberculosis (DOT – TB) at Kebumen District of Indonesia - Timbul Pranoto; Mora Claramita; I Dewa Putu Pramantara (Faculty of Medicine, Public Health, and Nursing, 2018)
Background: Tuberculosis (TB) is a major global health problem, even though TB can be prevented and treated. The WHO Global Tuberculosis Report 2015 reported 1.5 million deaths from TB, of which 1.1 million were TB with HIV-negative and 0.4 million were HIV-positive tuberculosis. As many as 25% of deaths from TB were in productive ages between 15 to 54 years. Low adherence is a major cause of treatment failure, drop-out and the rising number of cases of MDR (Multi Drugs Resistance). Adherence is also a key to improve the cure rate of treatment of TB patients. Home-based Direct Observer Treatment of patients with positive pulmonary Tuberculosis (DOT–TB) or in Bahasa Indonesia also known as Pengawas Minum Obat (PMO) may improve adherence and increase the TB cure rate and success rate. The DOT-TB has tasks to oversee, remind, motivate and assist TB patients who are undergoing the treatment process. Background of DOT–TB in improving adherence needs to be explored by examining their experiences, which can be expressed by using a phenomenological qualitative study to explore the meaning and significance of their experiences. Objectives: This study aimed to explore the efforts of DOT–TB in performing their duties, the constraints arising from these efforts, benefits, and expectations of the DOT–TB position.Methods: This study applied a qualitative approach with descriptive phenomenological methodology. The number of informants were 21 people divided into groups of DOT–TB whose patients were perfectly recovered (7 people), groups of DOT–TB whose patients were drop-out or failed (7 people) and a group of 7 TB programmers. Each group participated in the Focus Group Discussion (FGD) for 90-120 minutes.Results: The results of the study indicate that the presence of DOT–TB is very important and necessary in the management of TB. The biggest challenge of DOT–TBs in performing their duties are communication barriers due to differences in hierarchy and social status in the society. Their sense of hesitancy was a major challenge of DOT–TB in charge. According to respondents, the ideal DOT–TB is someone close to the patients, has patience, compassion, enough knowledge about TB and good communication skills.Conclusions: In order to perform their duties well, DOT–TBs require training concerning tuberculosis and communication.